The influence of relative pitch size on external load in professional men's soccer - Jäger, Johannes; Rumpf, Michael; Lochmann, Matthias (International Journal of Sports Science & Coaching, 2025)
This study aimed to investigate the influence of relative pitch size on external load parameters in professional soccer players during small-sided games (SSGs). Twenty-four professional male soccer players from the Greek first division participated in SSGs conducted over an eight-week period. The games were played on pitches of varying relative sizes (ranging from 45 to 184.62 m² per player), using two mini goals per side and a two-touch play restriction. External load metrics were recorded using by GPS units and included: (1) total distance covered; (2) high-intensity distance (≥ 15 km/h); (3) high-speed running distance (≥19.8 km/h); (4) distance covered within four predefined speed zones - Zone 3 (10.8–14.4 km/h), Zone 4 (14.5–19.8 km/h), Zone 5 (19.9–25.5 km/h), and Zone 6 (>25.5 km/h); (5) number of sprints; and (6) the number of accelerations and decelerations categorized as low (0–2.9 m/s²), moderate (3.0–3.9 m/s² or −3.0 to −3.9 m/s²), and high (>4.0 m/s² or < −4.0 m/s²). Generalized linear mixed models revealed positive associations between relative pitch size and all running-related load variables (βRange = 0.004 to 0.033, p < 0.05). Inverse relationships were observed for all acceleration bands and most deceleration bands (βRange = -0.001 to −0.011, p < 0.05), except for high-intensity decelerations (p = 0.374). Relative pitch size is a moderating factor for the external load in professional soccer players during SSGs. Increasing the relative pitch size can be used to augment external load, particularly by elevating running demands, whereas acceleration and deceleration activities are comparatively less influenced.
CRIS-Team Scopus Importer:2025-09-26
Keywords: Acceleration; association; football; global positioning system; high-speed running; small-sided games